Absorption spectra and electric field distributions of butterfly wing scale models coated with a metal film studied by finite-difference time-domain method - Pawin Raksrithong; Kitsakorn Locharoenrat (My University, 2019)
Inspired by alternative hybrid-biophotonic structures and modern computational electromagnetics in plasmonics, herein, we attempted to understand the plasmonic properties of a metal film (gold or palladium) on the surface features of butterfly wing scales, as they might represent the dominant features of structure-enhanced and/or structure-attenuated optical properties. Light-harvesting plasmonic antenna was loaded on these natural substrates. We examined the plasmonic properties of three models representing the scales of three lepidoptera species. Each scale model was assumed to have a 100 nm metal coating. In addition to the electron micrograph of the lepidopterans’ wings, the optical properties of the investigated structures were numerically studied using the finite-difference time-domain technique. We first constructed the biophotonic models of butterfly structures coated with a metal film, and then they were verified by scanning electron microscopy images using Lumerical Software, which provided an accurate solution of Maxwell’s equation for the micro/nanostructures. The metal samples were palladium or gold, while the investigated scales of butterfly species were Catopsilia pomona, Danaus genutia, and Cetbosia pentbesilea. Electric field and absorption spectra were observed under broadband light irradiations at perpendicular- and parallel-polarized light illuminations. As a result of the formation of variations of metals on the different features of wing scales, we observed changes in the absorption intensities and a redshift in the main peak absorbance. The spectra further showed a close relationship with the electric field distribution. A metal film coated on the butterfly wing scales acted as an optical plasmonic sensitivity to amplify and attenuate the visible light, whereas the existence of wave propagating modes from the well-defined structural variations resulted in a reduction and enhancement of the bandwidth of absorbance. Among the three simulation models, the Cetbosia pentbesilea scale model coated with a gold film demonstrated the best plasmonic properties to the electric field, in terms of its potential application for further biophotonic structure fabrication.
Keywords: Achromatic lens; Optical phenomena; Fern and Epiphyte Biology